ANALISIS STRATEGI BEKERJA MUNDUR DAN EKUIVALENSI PADA PERMASALAHAN NON RUTIN SISTEM PERSAMAAN - Fauziah, Asma' Nurul; Setiawan, Rubono (Jurnal Pendidikan Matematika dan Matematika SOLUSI, 2018)
Non-routine issues related to equation systems are often tested in National Mathematics Olympiad as well as College Entrance Test. The usual strategy to solve the system of equations is by the method of elimination, substitution, the mixture of elimination and substitution, and the method of graph or by substitution of variables from one equation to another so as to produce new equations and then searched the roots and newly substituted into things asked. But if the system of equations contains a higher rank of two, one tends to have difficulty in finding its roots, so another more efficient strategy is needed. The combination of backward-working strategies and applying equivalence in solving non-routine problems form the system of equations can be more effectively used. The purpose of writing this article is to know and analyze how the use of reverse working strategy and applying equivalence to solve system equality problems based on Polya step and analyze the effectiveness of the strategy. The type of research used in this study is Research and Development (RnD). From this article it can be concluded that the combination of strategies working backward and applying equivalence is quite effective because it does not take much time as well as fewer calculation steps in solving non routine problems of equation system